Re‐evaluation of the regulation of omeprazole in racehorses: An evidence‐based approach. Issue 3 (22nd February 2018) - Viljanto, M.; Hillyer, L.; Hincks, P.; Pearce, C.; Paine, S. W.
Abstract : Medication control and doping control have been established in horse racing to ensure the integrity of the sport and the welfare of the horses. This ensures that horses do not compete under the influence of any drugs, including omeprazole, a therapeutic medication used to treat equine gastric ulcer syndrome. In this study, pharmacokinetic data were produced in equine plasma and urine following an oral administration of 4 mg/kg of generic buffered formulation of omeprazole to six Thoroughbred horses in five daily doses to determine an appropriate screening limit and detection time in equine plasma and to assess whether the current detection time of 72 hr in equine urine would be applicable when an alternative omeprazole product is administered. C max of 436–2, 432 ng/ml and AUC0–tau of 1, 476–4, 371 ng hr ml −1 were obtained for plasma and indicated, in conjunction with other published oral omeprazole studies, that an appropriate plasma screening limit would be 500 pg/ml with a detection time of 48 hr. Urine analysis showed that omeprazole could be detected for up to 25 hr above the previously established urine screening limit of 500 pg/ml and thus indicated that the detection time advice could be potentially reduced from 72 to 48 hr to allow more comprehensive treatment of gastric lesions.